Legal Consideration, Death Penalty in the Perspective of Criminal Law and Buddhism in Indonesia - Warsito, Warsito; Sulaiman, Abdulah; Multiwijaya, Vientje Ratna (International Journal Labs, 2022)
Background: Uncertainty is being raised by Indonesia's discussion of the death penalty. The 2007 Constitutional Court ruling had a beneficial effect on society. The death penalty is being opposed more and more, particularly in European nations. Aim: The research aims to analyze legal consideration, death penalty in the perspective of criminal law and Buddhism in Indonesia. Method: The research makes use of a content analysis of the literature. Comparative law, legal history, legal theory, and legal principles are all included in the normative research. Findings: Buddhism's first and second stanzas of the Tipitaka, Dhammapada, and Danda Vaga Chapter X, p. 57, discuss the idea of punishment: Everyone dreads being punished and everyone dreads dying. One should not kill or commit murder after comparing oneself to others. Everyone values life and is afraid of punishment. One should not kill or commit murder after comparing oneself to others. The Dalai Lama, a well-known international figure, has also said that while life in prison is the best option from a humanitarian standpoint, the death penalty is the hardest punishment.